Molecular magnetic resonance imaging of activated hepatic stellate cells with ultrasmall superparamagnetic iron oxide targeting integrin αvβ3 for staging liver fibrosis in rat model - Wang, Deng-Bin; Zhang, Caiyuan; Liu, Huanhuan; Cui, Yanfen; Li, Xiaoming; Zhang, Zhongyang; Zhang, Yong (International journal of nanomedicine, 2016)
To evaluate the expression level of integrin αvβ3 on activated hepatic stellate cells (HSCs) at different stages of liver fibrosis induced by carbon tetrachloride (CCl4) in rat model and the feasibility to stage liver fibrosis by using molecular magnetic resonance imaging (MRI) with arginine-glycine-aspartic acid (RGD) peptide modified ultrasmall superparamagnetic iron oxide nanoparticle (USPIO) specifically targeting integrin αvβ3. All experiments received approval from our Institutional Animal Care and Use Committee. Thirty-six rats were randomly divided into three groups of 12 subjects each, and intraperitoneally injected with CCl4 for either 3, 6, or 9 weeks. Controls (n=10) received pure olive oil. The change in T2* relaxation rate (ΔR2*) pre- and postintravenous administration of RGD-USPIO or naked USPIO was measured by 3.0T clinical MRI and compared by one-way analysis of variance or the Student's t-test. The relationship between expression level of integrin αvβ3 and liver fibrotic degree was evaluated by Spearman's ranked correlation. Activated HSCs were confirmed to be the main cell types expressing integrin αvβ3 during liver fibrogenesis. The protein level of integrin αv and β3 subunit expressed on activated HSCs was upregulated and correlated well with the progression of liver fibrosis (r=0.954, P<0.001; r=0.931, P<0.001, respectively). After injection of RGD-USPIO, there is significant difference in ΔR2* among rats treated with 0, 3, 6, and 9 weeks of CCl4 (P<0.001). The accumulation of iron particles in fibrotic liver specimen is significantly greater for RGD-USPIO than naked USPIO after being injected with equal dose of iron. Molecular MRI of integrin αvβ3 expressed on activated HSCs by using RGD-USPIO may distinguish different liver fibrotic stages in CCl4 rat model and shows promising to noninvasively monitor the progression of the liver fibrosis and therapeutic response to antifibrotic treatment.